Soil organic carbon stocks in the forested regions of Mongolia and its mitigation potential - Ganbat, Byambaa; Ochirbat, Batkhishig; Guðmundsson, Jón; Turmunkh, Telmen; Khavtgai, Zoljargal; Ulgiichimeg, Ganzorig; Batsaikhan, Nyamdavaa (Geoderma Regional, 2025)
Soils represent the largest terrestrial carbon pool globally, with a significant proportion of this carbon stored in forest soils. Mongolia's forest area represents 0.45 % of the world's total forest cover. Research on the variability of SOC stocks within forest soil groups remains limited. This study aimed to address the SOC stock variations and retention capasities among groups of soils including Umbrisols (Gelic), Leptic Umbrisols, Mollic Umbrisols, Gleyic Umbrisols, and Podzols (Arenic). A total of 1558 soil samples from 316 soil profiles were collected in the Mongolian forest. The SOC stock was calculated from key parameters on SOC content, bulk density, and gravel content for each horizon. Then, the calculated SOC stock was standardized to the following depths: 0–30 cm, 30–60 cm, 60–100 cm, and 0–100 cm depth layers using a weighted average method. Mean SOC stock in 0–100 cm across all groups of forest soil was 88.5 Mg C ha−1. SOC stocks ranged between 59 and 141.0 Mg C ha−1 and varied significantly across soil groups (ANOVA: F = 22.9, p < 0.001). Gleyic Umbrisols, predominantly found on the northern foot slopes of mountain, exhibited the highest SOC stock. In contrast, Podzols (Arenic) in sandy forest areas had the lowest SOC stock. Leptic Umbrisols, the most widespread forest soil in Mongolia, had an average SOC stock of 78.6 Mg C ha−1. Across all soil groups, over 57.7–78.1 % of the SOC stocks was found in the first 30 cm emphasizing the critical role of this layer in carbon sequestration. The total SOC stock in Mongolian forest soils is estimated at approximately 1.24 petagrams (Pg). Furthermore, forest soils have the potential to sequester up to an additional 0.68 Pg of SOC. These results offer the first national scale SOC baseline for Mongolia's forests. The results on mitigation potentials highlight the importance of soil group specific management for carbon sequestration.